Girls and boys come out to stay : ideological formations in New Zealand-set children's fiction 1862-1917 : a dissertation presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Engliah at Massey University - Beets, Jacqueline (Massey University, 2003)
This dissertation examines ideological formations contained in children's fiction set in New Zealand and published between 1862 and 1917, considering forty-five primary texts (mostly novels, but also some short stories and picture-books) in light of their cultural background and relevant literary and postcolonial theory. The first three chapters discuss these works' representation of Maori, focusing upon a number of recurrent tropes and themes applicable to pakeha (European) desire for indigenisation in a colonised land; upon myths justifying dispossession of land from Maori; upon ideologies of Maori physical and moral degeneration (including cannibalism, savagery, alcoholism, and disease); and upon attitudes towards miscegenation. Chapter Four analyses the works as politically conservative middle-class propaganda which presents New Zealand as a means to financial, personal, and familial betterment for the emigrant of middling status. Chapter Five probes the texts' strongly evangelical spiritual and moral messages, which suggest the possibility of a utopian colonial settlement realised through pure young settlers. Chapter Six discusses presentations of gender roles and assumptions in this fiction, demonstrating to what extent it was receptive towards or even instigated fresh ideas for gender modelling in children's literature (for instance the feminised or androgynous boy and the active, assertive girl). Chapter Seven examines ways in which the texts advertise broad ideals of the British Empire, such as patriotism, military might, self-sacrifice or martyrdom, and imperialistic paternalism. Overall, the dissertation reveals early New Zealand-set children's fiction as perpetuating contemporary British ideological values through its intertextual recycling and repetition of familiar tropes and themes, thus making a significant contribution towards the wider corpus of postcolonial literature.
Keywords: Children's fiction; New Zealand fiction; Post-colonial fiction; Maori in literature; Imperialism in literature; New Zealand ideology